Biogas generation using Typha latifolia from phytoremediation trials of lead (Pb) contaminated water - Di Martino, Ana Maria; Butti, Mariano; Truchet, Daniela María; Franco, María del Rocío; Pérez, Débora Jesabel (INTA y Sbera, 2025)
Poster